PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI, KEMAMPUAN PERSONAL DAN PARTISIPASI MANAJEMEN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Rambis Kelia Lestari Br. Karosekali Karosekali; Afrah Junita; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This study aims to determine the effect of Information Technology Sophistication, Personal Ability and Management Participation on the Effectiveness of Accounting Information Systems at PT. Perkebunan Nusantara I Langsa). The population in this study is all parts of the field of work at PT. Perkebunan Nusantara I Langsa using SAP ERP. The sampling technique used the Proportionate Stratified Random Sampling method, data collection was carried out by distributing questionnaires to 79 respondents with criteria who were familiar with using the system and related to the system. The data analysis method uses Multiple Linear Regression (multiple regression analysis). The results of this study indicate that the sophistication of information technology has a significant effect on the effectiveness of accounting information systems, personal abilities have no significant effect on the effectiveness of accounting information systems and management participation has a significant effect on the effectiveness of accounting information systems. Based on the experience of researchers in the research process, there are several limitations in this study, such as the number of research respondents who are less, there are only 8 fields of work and the object of research is only one company so that it is still not enough to answer the actual situation and when collecting information and data through questionnaires. there are some employees who do not want to fill out the questionnaire. Other weaknesses experienced and become several factors that must be considered again for further researchers in order to improve their research by adding several more variables such as the perception variable about ease of use in order to further increase the effectiveness of the accounting information system.